The Function of Pantun in the Art Performace of Batang Hari Sembilan Solo Guitar during Sedekah Bumi Ceremony Held in Batu Urip Hamlet, South Sumatera - Andari, Imelda Tri; Suharto, Suharto (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
This study aims to describe the form and function of the solo guitar performance of Batang Hari Sembilan in Batu Urip hamlet, Batu Urip Taba village, Lubuklinggau city, South Sumatra. This study used a qualitative de-scriptive approach. Data collection techniques using observation, interviews, and documentation. The collected data were then analyzed using analytical and interactive techniques with data reduction, data presentation, and conclusion drawing. Based on the discussion that has been done, this study found that the Single Batang Hari Sembilan Guitar is a rhythm of guitar strings containing rhymes. Pantun is an identity and plays a very important role in the life of the community. The function of the pantun in the solo guitar performance of Batang Hari Sembilan was originally used as a communication function. Currently, this art performance has developed, namely as a ritual function, a function of preserving culture, a function of entertainment, a function of cultural continuity, a function of means of communication, and a function of emotional expression.